Alcohol Consumption in Ugandan HIV-infected Household-brewers Versus Non-brewers - Thakarar, Kinna; Asiimwe, Stephen B.; Cheng, Debbie M.; Forman, Leah; Ngabirano, Christine; Muyindike, Winnie R.; Emenyonu, Nneka I.; Samet, Jeffrey H.; Hahn, Judith A. (AIDS and Behavior, 2016)
The brewing of alcohol in Ugandan households is common, yet little is known about its relationship with alcohol consumption in HIV-infected individuals. We performed a cross-sectional analysis to assess the association between household brewing and unhealthy alcohol consumption among 387 HIV-infected adults in a prospective study examining the association between alcohol consumption and HIV-disease progression. Household brewing was defined as participants reporting that they or a household member home-brewed alcohol. Logistic regression was used to assess the association between household brewing and unhealthy alcohol consumption, defined as phosphatidylethanol (PEth) level ≥ 50 ng/ml or AUDIT-C (modified to measure the prior 3 months) positive. Sixty-six (17.0%) participants reported household brewing. Household brewers had higher odds of unhealthy alcohol consumption (AOR 2.27, 95% CI 1.26–4.12).
Keywords: Household brewing; Alcohol; HIV; Africa; Unhealthy alcohol use